Supply Chain Management / Strategy, Planning, and Operation - Chopra Sunil; Meindl Peter (Prentice Hall, 2001)
Building a Strategic Framework to Analyze Supply Chain, Planning Demand and Supply in a Supply Chain, Planning and Managing Inventories in a Supply Chain, Transportation and Network Design and Information Technology in a Supply Chain, Coordinating a Supply Chain and the Role of E-Business, Financial Factors Influencing Supply Chain Decisions, Name Index, Subject Index.
Building a Strategic Framework to Analyze Supply Chain, Planning Demand and Supply in a Supply Chain, Planning and Managing Inventories in a Supply Chain, Transportation and Network Design and Information Technology in a Supply Chain, Coordinating a Supply Chain and the Role of E-Business, Financial Factors Influencing Supply Chain Decisions, Name Index, Subject Index.